ChemInform Abstract: Copper‐Mediated One‐Pot Access to 2, 3‐Dihydrobenzo[b][1, 4]oxathiines from o, o′‐Dihydroxydisulfides. Issue 14 (April 2015) - Viglianisi, Caterina; Sinni, Aidona; Menichetti, Stefano
Abstract: o‐Thioquinones, generated via a copper‐mediated 1, 4‐elimination at sulfur of o, o′‐dihydroxy disulfides (I), are trapped in an inverse electron‐demand hetero Diels—Alder reaction with electron‐rich alkenes to give dihydrobenzooxathiines (II).